Modern and ancient pedogenesis as revealed by Holocene fire - Northern Apennines, Italy. (22nd February 2018) - Antisari, Livia Vittori; Agnelli, Alberto; Corti, Giuseppe; Falsone, Gloria; Ferronato, Chiara; Marinari, Sara; Vianello, Gilmo
Abstract: Soil needs a long time for its development, and traces of the past effects of climate, vegetation cover, and human activity can persist through time. Thus, paleosols are widely studied for paleo-environmental reconstructions, so to understand the effects of climate changes and/or human activities that for millennia transformed the land and interacted with soil formation. The aim of this work was to assess the influence of both ancient and modern environmental conditions on the pedogenesis at Mt Cimone, Northern Apennines, Italy. In particular, we compared buried paleosols and the overlying modern soils separated by a charcoal enriched horizon (Aub) along an altitudinal (climatic) sequence from 1553 to 1939 m above sea level. The radiocarbon age of the Aub horizon was 3040-2940 calibrated years before present, therefore it was taken as a chronological marker for the beginning of soil formation of the modern soil unit. The horizons thickness of the modern soil varied among the sites, suggesting the occurrence of accumulation/erosion processes, with a differential redistribution over the Aub horizon of the soil material transported by surface water runoff. The soil horizon sequence in the paleosol at lower altitudes (1553–1700 m) was rather simple (Bw-C horizons), indicating the occurrence of a moderately intense paleo-pedogenesis. Instead, from 1700 to 1900 m (mostly above the actual tree line) the paleosol showed well-expressed processes of eluviation-illuviation of organic matter and Fe/Al oxyhydroxides, which led to the formation of E-Bs or Bhs-C horizons sequences (podzols). These findings agree with previous studies dealing with climatic and palynological changes occurred in this area in the last seven millennia. At altitudes >1700 m, the ancient pedogenetic phase occurred during the Atlantic climatic period, with a cryic soil temperature regime, no permafrost, presence of seasonal snow, and a progressive tree species transition from Abies alba to oaks of warm temperate climate. The modern pedogenetic phase seemed to be affected by local wetter conditions and human induced forest disturbance, as it is testified by the change in the pollen abundance.